P457 A single dose of behaviour change: the impact of testing on behaviour and chlamydia transmission. (14th July 2019) - Wees, Daphne Van; Daas, Chantal Den; Heijne, Janneke; Kretzschmar, Mirjam
Abstract : Background: The aim was to explore short-term effects of chlamydia testing on sexual behaviour also taking into account psychological characteristics, and to estimate the impact on chlamydia transmission of interventions aimed at sustaining or enhancing testing effects. Methods: A cohort study was conducted among heterosexual STI clinic visitors aged 18–24 years. Risk classes based on behavioural and psychological characteristics, and transitions between classes three weeks after chlamydia testing, were identified using latent transition analysis. We developed a pair compartmental model with a susceptible-infected-susceptible structure informed by the cohort study. We estimated the impact of sustaining the found short-term effects of testing and of interventions enhancing these effects in those diagnosed, in those tested negative, or in all tested on chlamydia prevalence after five years relative to no effect. Results: Four classes were identified (n=810, 13% chlamydia positive (CT+)): 19% of people were in class 1 (5% CT+), 15% in class 2 (10% CT+), 47% in class 3 (16% CT+), and 19% in class 4 (17% CT+). The number of new partners in the past year was higher in class 3 and 4, compared to class 1 and 2. Class 2 and 4 had lower intentions to use condoms, reported less condom use, and were more impulsive, compared to class 1 and 3. Chlamydia positives were more likely to move to a lower risk class after testing, compared to chlamydia negatives. Sustaining this short-term effect resulted in an estimated relative reduction in chlamydia prevalence of 27%. The impact of interventions enhancing behaviour change in those tested negative (−45%) or in all tested (−48%) was estimated to be larger than in those diagnosed (−31%). Conclusion: Testing has strong short-term effects in chlamydia positives, but not in chlamydia negatives. Sustaining these effects is vital in controlling chlamydia transmission, as are interventions enhancing behaviour change in chlamydia negatives. Disclosure: No significant relationships.